The Use of Flipped Classroom Approach in Understanding Structure courses - Puspitasari, Tita (STKIP PGRI Tulungagung, 2025)
The flipped classroom is an innovative learning approach for teaching English grammar in Understanding Structure courses. The lecturer may provide the students with a PowerPoint or video to watch at home. The grammar principles are then applied in class through discussion, practice, and peer evaluation. With this approach, students are encouraged to learn at their own speed and arrive at class ready for more in-depth discussion. This research approach is a literature review, which entails examining a range of sources, including pertinent research findings and reference books, in order to develop underlying hypotheses. The flipped classroom has been shown to improve students' motivation, foster active engagement, and improve their understanding of grammar principles. Its efficacy, however, depends on having top-notch materials and students taking ownership of completing assignments before class.